Non-coding RNA transcriptome analysis of circulating human monocytes reveals subpopulation-enriched transcripts and selective isoforms differentially expressed during acute myocardial infarction. (25th November 2020) - Kratzer, A; Giral, H; Uyar, B; Franke, V; Moobed, M; Akalin, A; Landmesser, U
Abstract: Background: Acute inflammation leads to increased myelopoiesis in the bone marrow and recruitment of immune cells to respective sites of injury. Yet, in certain cases of high demand such as acute tissue damage as in acute myocardial infarction (AMI), innate immune cells can be additionally recruited from lymphoid organs such as the spleen. Monocytes are important in both onset and resolution of inflammation comprising a huge repertoire of coding and non-coding RNA molecules regulating a fast-acting immune response. Long non-coding RNAs (lncRNA) emerge as novel regulatory cell-specific molecules, which are able to influence cell physiology in numerous ways. Purpose: Delineate monocyte subpopulations from patients with AMI compared to healthy controls based on their non-coding transcriptome, different isoform usage and associated source of origin. Methods and results: Next generation bulk RNA sequencing has been performed from human monocytes after pre-sorting for CD14 expression and subsequent separation into three major subpopulations based on their surface markers CD14 and CD16 using a FACS Aria II cell sorter. Non-coding RNA expression shows clear differences between cells from healthy controls versus patients with AMI and among subpopulations. Intensive bioinformatics analysis revealed numerous annotated lncRNA, antisense, pseudogene and circular RNAs displaying significant differences in their expression profiles. Some lncRNA show positive or negative correlations with their respective coding antisense gene or their convergent or divergent sense neighbouring gene, such as linc02207 vs MCTP2, SAP30-AS vs SAP30, BID-AS vs BID, HLX-AS vs HLX or TNFAIP3-AS vs TNFAIP3. We also identified the existence of different isoforms of certain lncRNA and a distinct preference thereof, such as linc02207- 217 isoform being most abundant. Real-time PCR was applied for validation of lncRNA expression profile and their nucleocytoplasmic distribution observing preferential nuclear expression for most lncRNA. In vitro assays for silencing and overexpression approaches as well as treatment with inflammatory stimuli and in silico bioinformatics analysis will help to unravel their functionality. Additionally mapping our bulk RNA data to deconvoluted single cell RNAseq data from publicly available human cell atlas (HCA), is applied to additionally unravel the origin of particular subpopulations within the AMI monocytes, associating their origin to either spleen or bone marrow. Conclusions: High read depth bulk RNA sequencing revealed a human monocyte-specific long non-coding RNA transcriptome differentially expressed in three predefined subpopulations and disease stages. Distinct expression of lncRNA and associated coding genes as well as distinct isoform preference implies specific functionalities. Studying these molecules and their interaction partners will unravel functional participants in the development of therapeutic approaches for cardiovascular diseases. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): DZHK, SNF